2020
DOI: 10.1200/jco.19.01307
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab As Second-Line Therapy in Patients With Advanced Hepatocellular Carcinoma in KEYNOTE-240: A Randomized, Double-Blind, Phase III Trial

Abstract: PURPOSE Pembrolizumab demonstrated antitumor activity and safety in the phase II KEYNOTE-224 trial in previously treated patients with advanced hepatocellular carcinoma (HCC). KEYNOTE-240 evaluated the efficacy and safety of pembrolizumab in this population. PATIENTS AND METHODS This randomized, double-blind, phase III study was conducted at 119 medical centers in 27 countries. Eligible patients with advanced HCC, previously treated with sorafenib, were randomly assigned at a two-to-one ratio to receive pembro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

50
1,316
6
13

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,422 publications
(1,385 citation statements)
references
References 19 publications
50
1,316
6
13
Order By: Relevance
“…Keynote-240 confirmed the ORR observed in other single-agent PD-1 studies (16.9%) with a median duration of response of 13.8 months (95% CI 12.7-23.6). Despite an improvement in the two co-primary endpoints of OS (HR = 0.78, 95%CI: 0.61-0.99; p = 0.0238) and PFS (HR = 0.78, 95%CI: 0.61-0.99; p = 0.0209), the study failed to meet the prespecified threshold for statistical significance [109]. Amongst the reasons considered for the discrepancy between predicted and observed effects of pembrolizumab in this patient population is the rapidly changing landscape of systemic treatment in HCC, with the advent of novel therapies such as regorafenib and cabozantinib having changed the expected survival probability of patients with advanced HCC [110].…”
Section: Pd-1/pd-l1 Monotherapymentioning
confidence: 95%
“…Keynote-240 confirmed the ORR observed in other single-agent PD-1 studies (16.9%) with a median duration of response of 13.8 months (95% CI 12.7-23.6). Despite an improvement in the two co-primary endpoints of OS (HR = 0.78, 95%CI: 0.61-0.99; p = 0.0238) and PFS (HR = 0.78, 95%CI: 0.61-0.99; p = 0.0209), the study failed to meet the prespecified threshold for statistical significance [109]. Amongst the reasons considered for the discrepancy between predicted and observed effects of pembrolizumab in this patient population is the rapidly changing landscape of systemic treatment in HCC, with the advent of novel therapies such as regorafenib and cabozantinib having changed the expected survival probability of patients with advanced HCC [110].…”
Section: Pd-1/pd-l1 Monotherapymentioning
confidence: 95%
“…The most frequent serious adverse events were increased serum transaminases and adrenal insufficiency. The final analyses of the phase-3 RCT KEYNOTE-240 evaluating pembrolizumab versus placebo as a second-line treatment in western HCC patients showed an improvement in the co-primary endpoints OS and PFS; however, these differences did not reach statistical significance per specified criteria [29].…”
Section: Immunotherapy: Immune Checkpoint Inhibitorsmentioning
confidence: 97%
“…Based on this data, pembrolizumab was granted accelerated approval by the FDA in November 2018 as a second-line treatment after sorafenib. A phase III trial (KEYNOTE-240) comparing pembrolizumab to a placebo as a second-line treatment demonstrated that pembrolizumab was associated with a longer median OS and PFS; however, these findings were not deemed statistically significant according to the prespecified statistical plan [34]. Two further phase III trials are currently ongoing: KEYNOTE-394 is evaluating pembrolizumab versus a placebo and best supportive care in Asian patients with systemically treated advanced HCC, while KEYNOTE-937 is evaluating pembrolizumab versus a placebo as an adjuvant therapy in HCC patients after curative treatment.…”
Section: Ici Monotherapies Directed Against Pd-1 and Ctla-4mentioning
confidence: 99%